Morphometric Study of Renal Vasculature with Multidetector Computed Tomography - Giri, Rohit Kumar; Regmi, Shubhekshya; khadka, Hensan (Medical Journal of Eastern Nepal, 2025)
Background: The end-stage renal disease is a public health problem with an increasing incidence rate and preoperative evaluation of renal vessels is important for transplant. The arteries and veins differ in terms of their level of origin, size, obliquity, level of confluence, tributaries, and relationships. The purpose of the study was to examine how common different anatomical variations in the renal vessels are, using Triple phase Contrast Enhanced Computed Tomography (CECT). Methods: A cross-sectional observational study was conducted. A total of 89 patients undergoing Triple Phase CECT of the abdomen and pelvis who met inclusion criteria were evaluated following ethical clearance from the Institutional Review Board (IRB), NAMS. The number of renal arteries and veins, the diameter of the renal artery, the distance from the renal artery’s origin to its first bifurcation, the distance from the inferior vena cava to the confluence of the right renal vein, and the distance between the confluence of the left renal vein and aorta were measured, and descriptive analysis was done. Results: The prevalence of multiple renal arteries was 39 (43.82%-right kidney: 18 cases, left kidney: 21 cases). Hilar arteries were found in 16 right kidneys and 18 left kidneys, and polar arteries were found in 3 right kidneys and 4 left kidneys. Early renal artery bifurcation was identified in 11 right kidneys and 18 left kidneys. Sixteen kidneys had a double right renal vein, one had a double left renal vein, and one had a triple right renal vein. One kidney had retroaortic left RV whereas 35 right kidneys and 10 left kidneys had late venous confluence. Conclusion: MDCT is a non-invasive, effective imaging method to evaluate renal vascular anatomy and their variations for preoperative evaluation. It provides exact information regarding renal vasculature and is crucial for preoperative planning in renal surgeries and transplantation. Therefore, this study might contribute information regarding kidneys, renal vasculature and variations and help surgeons to reduce the chance of any surgical complications.